Chitosan tubes enriched with fresh skeletal muscle fibers for delayed repair of peripheral nerve defects - Crosio, Alessandro (Neural Regen Res, 2019)
Nerve regeneration after delayed nerve repair is often unsuccessful. Indeed, the expression of genes associated with regeneration, including neurotrophic and gliotrophic factors, is drastically reduced in the distal stump of chronically transected nerves; moreover, Schwann cells undergo atrophy, losing their ability to sustain regeneration. In the present study, to provide a three-dimensional environment and trophic factors supporting Schwann cell activity and axon re-growth, we combined the use of an effective conduit (a chitosan tube) with a promising intraluminal structure (fresh longitudinal skeletal muscle fibers). This enriched conduit was used to repair a 10-mm rat median nerve gap after 3-month delay and functional and morphometrical analyses were performed 4 months after nerve reconstruction. Our data show that the enriched chitosan conduit is as effective as the hollow chitosan conduit in promoting nerve regeneration, and its efficacy is not statistically different from the autograft, considered the “gold standard” technique for nerve reconstruction. Since hollow tubes not always lead to good results after long defects (> 20 mm), we believe that the conduit enriched with fresh muscle fibers could be a promising strategy to repair longer gaps, as muscle fibers create a favorable three-dimensional environment and release trophic factors. All procedures were approved by the Bioethical Committee of the University of Torino and by the Italian Ministry of Health (approval number: 864/2016/PR) on September 14, 2016.